Gods of Egypt - Proyas, Alex, 1963-; Sazama, Matt; Sharpless, Burk; Iwanyk, Basil; Coster-Waldau, Nikolaj, 1970-; Thwaites, Brenton, 1989-; Boseman, Chadwick; Yung, Elodie, 1981-; Eaton, Courtney, 1996-; Sewell, Rufus, 1967-; Butler, Gerard, 1969-; Rush, Geoffrey, 1951-; et al. (Santa Monica, California : Summit Entertainment, 2016)
In this spectacular action-adventure inspired by the classic mythology of Egypt, the survival of mankind hangs in the balance as an unexpected mortal hero Bek undertakes a thrilling journey to save the world and rescue his true love. In order to succeed, he must enlist the help of the powerful god Horus in an unlikely alliance against Set, the merciless god of darkness, who has usurped Egypt's throne, plunging the once peaceful and prosperous empire into chaos and conflict.
Special features: The Battle for Eternity: stunts -- A Window into Another World: visual effects. Blu-ray exclusives: Deleted storyboards -- A Divine vision: creating a cinematic action fantasy -- Of gods and mortals: the cast -- On location: shooting in Australia -- Transformation: costume, make-up & hair.
Originally released as a motion picture in 2016.
Widescreen (2.40:1)
Special features: The battle for eternity: stunts; A window into another world: visual effects.
Director of photography, Peter Menzies Jr. ; production designer, Owen Paterson ; editor, Richard Learoyd ; music, Marco Beltrami.
Nikolaj Coster-Waldau, Brenton Thwaites, Chadwick Boseman, Elodie Yung, Courtney Eaton, Gerard Butler, Geoffrey Rush, Bryan Brown, Rufus Sewell.
MPAA rating: PG-13.
Keywords: Gods, Egyptian -- Drama; Spanish dialogue; Spanish subtitles; Civilization; Action and adventure films; Egypt -- Civilization -- Drama; Egypt; Feature films; Action and adventure films; Fiction films; Fantasy films; Science fiction films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; DVD-Video discs; Videodiscs; DVDs; Drama